Tutela urgente satisfativa de efeitos irreversíveis : entre a regra processual e a tutela dos direitos - Pozatti, Fabrício Costa (2017)
This study aims to analyze the way the Brazilian legal system grants judicial protection to those situations of the life where the rights need immediate remedy, but the correspondent judicial decision might result in irreversible effects. The intention is to demonstrate the incompatibility between the procedural rule contained in Article 300, paragraph 3°, of the Code of Civil Procedure, and the civil lawsuit’s objective of serving as a tool capable of safeguarding legal rights adequately, effectively and timely. Based on this premise, this study argues both for the flexibility of the procedural rule in light of the particularities of the case and the need for the judge to favor the one party’s likelihood of success on the merits in detriment of the opposing party’s non-likelihood of success on the merits. In order to assess the level of likelihood necessary to grant the preliminary injunction, the judge must balance the conflicting interests and values as well as the extension of possible harms to the rights of the parties, applying, to further such evaluation, the normative postulates, principally the postulate of proportionality.